2015
DOI: 10.1007/s10571-015-0288-1
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism Within the 3′UTR of NLRP3 is Associated with Susceptibility for Ischemic Stroke in Chinese Population

Abstract: Stroke was regarded as a severe disorder with high morbidity and high mortality worldwide, ischemic stroke (IS) accounts for 85 to 90 % of new increased stroke cases. Partial mechanisms were elucidated by genetic factors including genomic instability such as single nucleotide polymorphism (SNP). Previous reports demonstrated that inflammation was involved in IS, NLRP3 [nucleotide-binding domain (NOD)-like receptor protein 3], acting as a specific inflammatory gene, however, its function and influence on IS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
6
17
0
Order By: Relevance
“…Previous studies have shown that there is an association between NLRP3 gene polymorphisms and susceptibilities to certain diseases, including Crohn's disease [ 14 ], abdominal aortic aneurysms [ 15 ], and late-onset Alzheimer's disease [ 20 ]. The influence of an NLRP3 gene polymorphism on ischemic strokes was also shown in Zhu et al's study [ 16 ]. LAA ischemic stroke is the most common type of ischemic stroke and is primarily caused by atherosclerosis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous studies have shown that there is an association between NLRP3 gene polymorphisms and susceptibilities to certain diseases, including Crohn's disease [ 14 ], abdominal aortic aneurysms [ 15 ], and late-onset Alzheimer's disease [ 20 ]. The influence of an NLRP3 gene polymorphism on ischemic strokes was also shown in Zhu et al's study [ 16 ]. LAA ischemic stroke is the most common type of ischemic stroke and is primarily caused by atherosclerosis.…”
Section: Discussionsupporting
confidence: 59%
“…NLRP3 gene mutations are also observed to be associated with rheumatoid arthritis [ 13 ], Crohn's disease [ 14 ], and abdominal aortic aneurysms [ 15 ]. One study from China suggested that genetic polymorphisms in NLRP3 may influence the risk of ischemic stroke in the Chinese population [ 16 ]. To the best of our knowledge, there are limited studies regarding the relationship between NLRP3 polymorphisms and susceptibility for LAA stroke and MES in the Chinese Han population.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1b and/or NLRP3 polymorphisms and changes in gene expression are associated with depression, migraine, MS, AD, PD and ischaemic stroke in patients. 28,[57][58][59][60][61][62][63] Similarly, NLRP3 polymorphisms are associated with risk of hypertension and age-related increase of blood pressure, type 2 diabetes, coronary heart disease and acute vascular events. [64][65][66][67] Increased caspase-1 activation is seen in the brain of AD patients and the NLRP3 inflammasome was found to contribute to disease progression and changes in cognitive function in rodents.…”
Section: Structure and Activation Of Inflammasomesmentioning
confidence: 99%
“…The NOD (nucleotide-binding oligomerization domain)-like receptor (NLR) pyrin-domain-containing 3 (NLRP3) inflammasomes are abundantly expressed in the brain and immune cells. Recent findings demonstrate the participation of NLRP3 in ischemic stroke [6][7][8][9] . These findings indicate that NLRP3 inflammasomes may play an important role in detecting cellular damage and mediating inflammatory responses to aseptic tissue injury during ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%